2019
DOI: 10.1017/s1368980018003920
|View full text |Cite
|
Sign up to set email alerts
|

The intergenerational transmission of family meal practices: a mixed-methods study of parents of young children

Abstract: ObjectiveThe current mixed-methods study explored qualitative accounts of prior childhood experiences and current contextual factors around family meals across three quantitatively informed categories of family meal frequency patterns from adolescence to parenthood: (i) ‘maintainers’ of family meals across generations; (ii) ‘starters’ of family meals in the next generation; and (iii) ‘inconsistent’ family meal patterns across generations.DesignQuantitative survey data collected as part of the first (1998–1999)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Our findings demonstrated that all three of these factors were commonly and consistently considered across time, albeit at varying levels of priority, often requiring trade-offs to make the family meal achievable. While these challenges are acknowledged in media and research, the strategies that are promoted to overcome them, such as engaging in meal planning, using shopping lists, purchasing and cooking foods in bulk or utilizing leftovers ( Fiese et al, 2012 ; Berge et al, 2013 ; Alm & Olsen, 2017 ; Loth et al, 2019 ), were rarely used consistently or effectively by participants across either time point. Contemporary solutions are offered in online services and technology ( Hertz & Halkier, 2017 ; Fuentes & Samsioe, 2020 ; Laila et al, 2023 ), and prior research has indicated that these services can reduce time burden and simplify meal preparation ( Hertz & Halkier, 2017 ; Fuentes & Samsioe, 2020 ; Oberle et al, 2020 ; Carman et al, 2021 ; Fraser et al, 2021 ; Laila et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that all three of these factors were commonly and consistently considered across time, albeit at varying levels of priority, often requiring trade-offs to make the family meal achievable. While these challenges are acknowledged in media and research, the strategies that are promoted to overcome them, such as engaging in meal planning, using shopping lists, purchasing and cooking foods in bulk or utilizing leftovers ( Fiese et al, 2012 ; Berge et al, 2013 ; Alm & Olsen, 2017 ; Loth et al, 2019 ), were rarely used consistently or effectively by participants across either time point. Contemporary solutions are offered in online services and technology ( Hertz & Halkier, 2017 ; Fuentes & Samsioe, 2020 ; Laila et al, 2023 ), and prior research has indicated that these services can reduce time burden and simplify meal preparation ( Hertz & Halkier, 2017 ; Fuentes & Samsioe, 2020 ; Oberle et al, 2020 ; Carman et al, 2021 ; Fraser et al, 2021 ; Laila et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Family meals that parents remember as children influenced their current family meals with their own children 26,27 . For instance, the types of food, the norms and cultures could transmit from generation to generation.…”
Section: Discussionmentioning
confidence: 99%
“…Trofholz (38) found that the lessons mothers learned about family meals from their parents influenced the lessons they shared with their school-aged children. Loth and colleagues (41) recently described the intergenerational transmission of mealtime routines based on the frequency of participation using three different longitudinal trajectories from adolescence to adulthood: maintainers, starters and inconsistent. Those who were considered maintainers of regular family meals reported many of the same mealtime supports that were discussed by parents with a 'Togetherness' orientation, including positive childhood memories about family meals and having a partner who shared a similar upbringing with family meal participation or who also valued family meals.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the well-known barriers to family meals, including a lack of time, conflicting schedules and picky eaters (34)(35)(36) , recent nutrition research highlights the importance of intergenerational influences on family meal routines (37)(38)(39)(40)(41)(42) . This small body of literature emphasizes that both positive and negative childhood mealtime experiences influence how and whether parents engage in mealtimes with their own families (38,39,41) . For example, Loth and colleagues (41) described from a nutrition perspective, how parents who participated in frequent family meals from adolescence to adulthood experienced more positive early life experiences and supports (related to cooking skills, family togetherness and relationships), as compared with those who had inconsistent family meal patterns across time.…”
mentioning
confidence: 99%